Dictionary of computing and communications (McGraw-Hill, 2003)
Features 11000 entries encompassing the language of computer science, information technology, and communications; Includes synonyms, acronyms, and abbreviations; Provides pronuncations for all terms; Covers such topics as computer science, communications, aerospace and other fields of engineering, control systems, electromagnetism, electronics, navigation, optics, and systems engineering; Includes an appendix containing measurement conversion tables, tables of useful data, and charts.